2017
DOI: 10.1002/hbm.23753
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological correlates of the drift diffusion model in visual word recognition

Abstract: This study was designed to explore the electrophysiological correlates of the diffusion models drift rate parameter in cognitive decision making. Eighty-two participants completed a lexical decision task while their stimulus-dependent event-related potentials (ERP) and theta frequency band power were measured. A mass univariate approach was applied to examine the timeline at which correlations were evident. Individual differences in drift rate parameter and condition-wise within-subject differences in drift ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
2
4
0
Order By: Relevance
“…Increased theta-band power was associated with faster response execution times in the combined sample and within both BD and HC groups. This is consistent with prior findings regarding theta power during visual face processing in BD (Lasagna et al, 2021), as well as simulation and non-clinical studies indicating relationships between theta oscillations and processing speed/efficiency (Mueller et al, 2017;Smerieri et al, 2010;van Vugt et al, 2012). Across the combined sample and within only BD participants, increased power was also associated with greater discrimination (d') of facial expressions and stronger tendency to respond.…”
Section: Discussionsupporting
confidence: 92%
“…Increased theta-band power was associated with faster response execution times in the combined sample and within both BD and HC groups. This is consistent with prior findings regarding theta power during visual face processing in BD (Lasagna et al, 2021), as well as simulation and non-clinical studies indicating relationships between theta oscillations and processing speed/efficiency (Mueller et al, 2017;Smerieri et al, 2010;van Vugt et al, 2012). Across the combined sample and within only BD participants, increased power was also associated with greater discrimination (d') of facial expressions and stronger tendency to respond.…”
Section: Discussionsupporting
confidence: 92%
“…We also found that faster-but not more accurate-responses were associated with increased theta power and theta-gamma PAC. These findings align with results from simulations and non-clinical samples showing relations between theta oscillations and processing speed/efficiency (Mueller et al, 2017;Smerieri et al, 2010;van Vugt et al, 2012). In those studies, decreased theta was associated with slower/less efficient processing.…”
Section: Potential Mechanisms Of Reduced Theta Power/theta-gamma Pacsupporting
confidence: 88%
“…Instead of running statistical analysis on RTs per se , we computed variables of interest resulting from a DDM analysis of RTs, as described in “Introduction” section. These DDM parameters were computed on RTs for correct and incorrect answers using Fast-dm software (Voss et al, 2004 ; Voss and Voss, 2007 ) after excluding RTs greater than mean + 3 SD on an intra-individual basis for each condition separately, along the same lines as other authors aiming to investigate the electrophysiological correlates of decision-making with diffusion models (e.g., Mueller et al, 2017 ). DDM is typically applied to two alternative decision tasks, whereas in our case we used a five (emotional expressions) forced-choice task.…”
Section: Methodsmentioning
confidence: 99%